The phenomenon of shame as the psychological genesis of life-creation - KOPYLOV, Denis (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Dynamic processes in the contemporary Ukrainian socio-political context intensify the psychological effects of prolonged uncertainty and crisis, forcing individuals to construct life strategies amid unstable social reference points. In such conditions, life-creation becomes a key resource for preserving personal integrity and development, though its genesis is interpreted differently across major psychological traditions. This article aims to clarify the content and structure of the genesis of personal life-creation in contemporary psychology and to identify the emotional factor capable of initiating or blocking the subject’s life construction. Methods. The study applies theoretical and methodological analysis, synthesis, comparison, generalization, and conceptualization. The material is interpreted through the coherence of emotional, cognitive, and behavioral components of life-creation. Results. Life-creation is shown to have multiple forms of genesis. Within the humanistic-existential tradition, it is rooted in meaning, authenticity, freedom, and responsibility; within the behaviorist and social-cognitive tradition, in learning, self-regulation, modeling, and adaptation; within the psychoanalytic tradition, in the transformation of the unconscious, symbolization of experience, and sublimation; and within the personological-developmental approach, in integrating events and decisions into a biographical perspective, goal-setting, and the act. The article substantiates the assumption that shame serves as a system-forming source within the emotional component of life-creation, determining the coherence of its elements. Functional shame fulfills a regulatory social role and supports the integrity of the Self. In contrast, toxic shame, as an introjected dominant, distorts meaning-making, narrows freedom of choice, blocks activity, disrupts interoceptive sensitivity, and leads to the phenomenon of “frozen agency” and loss of subjectivity. Conclusions. Life-creation should be understood as both a process and an outcome of aligning meaning and action, as well as internal and external conditions, primarily shaped by emotional regulation. Toxic shame functions as an antagonist of life-creation by positioning the individual as an object of evaluation and paralyzing life authorship. Conversely, the integration of shame and the restoration of impulse, action, creativity, and subjectivity create conditions for a return to active construction of one’s life space.